TELAAH KRITIS TENTANG LEMBAGA PENGAKUAN ANAK (STUDI KRITIS ANTARA HUKUM ISLAM DAN HUKUM POSITIF) - Ahmad Darbi B. (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
The position of the rights of children in child recognition institutions of Islamic law that children born of marriage outside of marriage / outside of marriage are declared valid if the birth of the child is above six months, if less than six months, the child is declared an illegitimate child in a child recognition institution . This is based on QS. al-Ahqaf verse 15 which explains the pregnancy period and breastfeeding period combined then 30 (thirty) months, as well as in QS. Luqman verse 14 describes the breastfeeding period for two years (24 months). Then the deduction from the deduction is six months, as a minimum limit of pregnancy. Whereas in positive law it implies that legitimate children are children born within or due to legal marriage. So, as long as the marriage is legal, the child born is stipulated in a child recognition institution as a legitimate child, provided that the child's father confesses to committing adultery before his marriage takes place. This is based on the substance of KHI Article 99 and Law Number 1 Year 1974 Article 42. Then the Civil Code includes the validity of the child on the argument stating that the inheritance rights of the child out of wedlock will arise after the recognition and ratification.